Prophet, Intermediary, King : The Dynamics of Mediation in the Biblical World and Old Babylonian Mari - Deluty, Julie B. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
In Prophet, Intermediary, King: The Dynamics of Mediation in the Biblical World and Old Babylonian Mari , Julie B. Deluty investigates the mediation of prophecy for kings in biblical narratives and the Old Babylonian corpus from Mari. In many cases, the prophet's message is delivered through a third party-sometimes a royal official or family member-who may exercise a degree of autonomy in the transmission of the words. Drawing on social network theory, the book highlights the importance of third-party intermediaries in the process of communication that lies at the core of biblical and ancient Near Eastern prophecy. Recognition of the place of non-prophetic intermediaries in a monarchic system offers a new dimension to the study of prophecy in antiquity.